Epidemiological and Genetic Characteristics of Rabies Virus Transmitted Through Organ Transplantation - Chen, Jingfang; Liu, Guang; Jin, Tao; Zhang, Rusheng; Ou, Xinhua; Zhang, Heng; Lin, Peng; Yao, Dong; Chen, Shuilian; Luo, Meiling; Yang, Fan; Huang, Dana; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
In January 2016, two patients died of rabies after receiving kidney transplants from a common organ donor at a hospital in Changsha, Hunan, China. The medical records, epidemiological data of the organ donor, two kidney and a liver recipients were reviewed. Intravitam saliva samples of the two kidney recipients were tested for rabies virus (RABV) using real-time RT-PCR, and the nucleoprotein (N) gene was amplified and sequenced by Sanger sequencing. Whole genome sequences were analyzed using next-generation sequencing. The N genes of the two kidney recipients showed 100% nucleic acid identity. Phylogenetic analysis of the complete genome, N and glycoprotein (G) genes indicated that the RABV was homologous with dog isolates from the Hunan province and belong to the China I lineage, which is widespread in China. The organ donor was a 22-month-old boy who died from unknown acute progressive encephalitis. After undergoing sub-hypothermia hibernation therapy, rabies-associated symptoms were atypical, and rabies was neglected because serum RABV-specific antibodies were negative. An unknown wound on the forehead of the donor was found two months before the onset of symptoms. Based on the clinical, epidemiological, and molecular findings, we speculated that the RABV initially originated in the donor from a dog bite, and was then transmitted to the recipients by organ transplantation. An uncertain exposure history and misdiagnosis played important roles in the spread of the RABV. Rabies should be considered in patients with acute progressive encephalitis of unexplained etiology, especially in potential organ donors.